Pengaruh Stres Kerja, Beban Kerja, Dan Kepuasan Kerja Terhadap Kinerja Karyawan Di PT Sumber Alfaria Trijaya, Tbk Cabang Area Buduran Sidoarjo - Ivana Mei Yulianti; Tri Wahjoedi; Parwita Setya Wardhani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the effect of work stress, workload and job satisfaction on employee performance at PT. Sumber Alfaria Trijaya Tbk Area Branch Buduran Sidoarjo. This type of research is quantitative. The population studied in this study were all employees at PT. Sumber Alfaria Trijaya Tbk Area Branch Buduran Sidoarjo. The number of samples in this study was 86 respondents. The sample collection technique in this study was carried out by probability sampling. The data collection technique used in this study was a questionnaire distributed to all employees of PT. Sumber Alfaria Trijaya Tbk Area Branch Buduran Sidoarjo. The data analysis technique used in this study was multiple linear regression analysis using SPSS (statistical Product and Services Solution) software version 29.0. The results of the study indicate that the work stress variable has a positive and significant effect on employee performance with a t-count value = 7.547> t-table 1.989, the workload variable has a positive and significant effect on employee performance with a t-count value = 7.121> t-table 1.989, and the job satisfaction variable has a positive and significant effect on employee performance with a t-count value of 6.158> t-table 1.989. From the three results, it shows that work stress, workload and job satisfaction on employee performance have a partial effect. For simultaneous testing, the results obtained that all variables together have a significant effect on employee performance